High-toughness concrete sidewalk brick as well as preparation method and application thereof

By adding modified fly ash, mineral fibers and organic fibers to the concrete of sidewalk bricks, the problem of insufficient crack resistance, seepage and freeze-thaw resistance during long-term use of existing sidewalk bricks is solved, and the preparation of high-tough concrete sidewalk bricks is achieved, with excellent compressive, crack resistance, seepage and freeze-thaw resistance.

CN119841603AInactive Publication Date: 2025-04-18SICHUAN HIGHWAY PLANNING SURVEY DESIGN AND RESEARCH INSTITUTE LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510338614.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing sidewalk bricks are difficult to maintain crack resistance, seepage resistance and freeze-thaw resistance during long-term use, resulting in frequent repairs and replacements.

Method used

High-tough concrete sidewalk bricks are prepared by adding modified fly ash, mineral fibers and organic fibers to the concrete, and reasonably designing the aggregate and water-gluing ratio, and using high-temperature calcination and ball milling treatment.

Benefits of technology

The high-tough concrete sidewalk bricks have excellent crack resistance, seepage resistance and freeze-thaw resistance cycling properties on the basis of meeting compressive strength, reducing the shrinkage rate and cracking risk of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, and particularly discloses a high-toughness concrete sidewalk brick and a preparation method and application thereof.The high-toughness concrete sidewalk brick is prepared from, by weight, 500-600 parts of cement, 200-300 parts of modified fly ash, 200-300 parts of mineral fiber, 30-40 parts of organic fiber, 1000-1200 parts of aggregate, 3-5 parts of water reducing agent and 100-150 parts of water; wherein the modification process of the modified fly ash comprises the following steps: mixing fly ash, calcium oxide and sodium carbonate by adopting a ball mill, and then carrying out high-temperature calcination; wherein the aggregate comprises coarse aggregate and fine aggregate. The high-toughness concrete sidewalk brick disclosed by the invention has excellent crack resistance, impermeability and freeze-thaw cycle resistance on the basis of meeting the compressive strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete, and in particular to a high-toughness concrete sidewalk brick and a preparation method and application thereof. Background Art

[0002] Concrete is widely used in various municipal construction and public facilities, such as highways, urban roads, square parks, commercial blocks, parking lots, parks and green spaces, etc. Among them, sidewalk bricks are a common concrete product used in municipal construction and public facilities.

[0003] Most sidewalk bricks are exposed to the outdoors and are exposed to the sun, rain and other natural factors for a long time. In order to ensure that sidewalk bricks can maintain beauty, durability and stability under various environmental conditions, higher requirements are placed on the basic performance of sidewalk bricks, requiring them to have excellent crack resistance, impermeability and freeze-thaw cycle resistance, so that they can maintain stable performance during long-term use and reduce the frequency of maintenance and replacement. For some special scenes, it is necessary to carve patterns with a certain aesthetic on the sidewalk bricks, requiring the sidewalk bricks to have a certain toughness. Summary of the invention

[0004] The object of the present invention is to provide a high-toughness concrete sidewalk brick which has excellent crack resistance, impermeability and freeze-thaw cycle resistance on the basis of meeting the compressive strength requirements.

[0005] In addition, the present invention also provides a preparation method and application of the high-toughness concrete sidewalk bricks.

[0006] The present invention is achieved through the following technical solutions: A high-toughness concrete sidewalk brick comprises the following components in parts by weight: 500-600 parts of cement, 200-300 parts of modified fly ash, 200-300 parts of mineral fiber, 30-40 parts of organic fiber, 1000-1200 parts of aggregate, 3-5 parts of water reducer, 100-150 parts of water; The modification process of the modified fly ash is as follows: fly ash, calcium oxide and sodium carbonate are mixed by ball milling, and then calcined at high temperature; Among them, aggregate includes coarse aggregate and fine aggregate.

[0007] The present invention can hinder the expansion of cracks inside concrete and the formation of macro cracks by adding fibers to concrete, and can reduce the cracking shrinkage rate of concrete, that is, it can reduce the drying shrinkage of concrete and improve the crack resistance of concrete. The present invention adds mineral fibers and organic fibers to concrete at the same time, wherein the mineral fibers have excellent properties of high strength, corrosion resistance and high temperature resistance, and the organic fibers have high tensile strength and elastic modulus, and have excellent impact resistance, chemical corrosion resistance, wear resistance and bending resistance. The present invention uses organic fibers with high tensile properties and mineral fibers with high compressive properties in combination, which can greatly reduce the cracking shrinkage rate of concrete compared with the use of single fibers; and by reasonably adding the amount of mineral fibers and organic fibers, the shrinkage rate of concrete can be reduced to the greatest extent. Preferably, the amount of mineral fibers is 10-20% based on the total weight of cement and aggregate; the amount of organic fibers is 1.6-2.7%. The tensile strength of the high-toughness concrete sidewalk bricks prepared by the present invention is greater than 14MPa, indicating that it has high toughness. Generally, concrete with a tensile strength greater than 7MPa is high-toughness concrete.

[0008] On the one hand, the present invention adopts a method of using a composite of coarse aggregate and fine aggregate as aggregate, adopts density stacking theory to reasonably design the amount of coarse aggregate and fine aggregate, and reasonably controls the water-cement ratio and adds a water reducer, thereby improving the density of concrete, its impermeability and freeze-thaw cycle resistance to a certain extent; on the other hand, the present invention adds fly ash to concrete, and when water exists at room temperature, the fly ash can react secondary with the components in the concrete to generate a hydrated calcium silicate gel that is insoluble in water. This reaction not only reduces the possibility of dissolution, but also fills the pores inside the concrete, thereby improving the strength and impermeability of the concrete; although the addition of fly ash can improve the density of concrete, thereby improving the impermeability and freeze-thaw resistance, due to the relatively low strength of fly ash, excessive addition will lead to an increase in the replacement ratio of cement, thereby reducing the overall strength of the concrete. Therefore, the present invention uses modified fly ash modified by calcium oxide and sodium carbonate. The fly ash contains SiO2, Al2O3, FeO, Fe2O3, CaO, TiO2, etc. The calcium oxide of the present invention can excite the active components (Al2O3, SiO2) in the fly ash, thereby improving the activity of the fly ash; if only calcium oxide is used, Al2O3 and SiO2 in the fly ash cannot be well released; the present invention can promote the excitation of fly ash by calcium oxide at high temperature by using calcium oxide and sodium carbonate in combination, and grinding first can increase the specific surface area of ​​the powder and change the surface structure of the fly ash, which is beneficial to the excitation of fly ash by calcium oxide during subsequent high-temperature calcination.

[0009] Therefore, compared with unmodified fly ash, under the same dosage conditions, the modified fly ash can better react with the components in the high-toughness concrete sidewalk bricks to form hydrated calcium silicate gel, filling the internal pores of the concrete. That is, the modified fly ash used in the present invention can improve the impermeability and freeze-thaw resistance of the high-toughness concrete sidewalk bricks under the condition of less dosage, and can further reduce the shrinkage rate of the high-toughness concrete sidewalk bricks, and has little effect on the compressive strength of the high-toughness concrete sidewalk bricks.

[0010] In summary, the high-toughness concrete sidewalk brick of the present invention has excellent crack resistance, impermeability and freeze-thaw cycle resistance on the basis of meeting the compressive strength requirements.

[0011] In a preferred embodiment, the weight ratio of fly ash, calcium oxide and sodium carbonate is 100:(10-15):(2-5).

[0012] The dosage of calcium oxide and sodium carbonate has a great influence on the modification effect of fly ash. The above-mentioned proportions of fly ash, calcium oxide and sodium carbonate can achieve better modification of fly ash.

[0013] In a preferred embodiment, the high temperature calcination temperature is 350-400°C.

[0014] In a preferred embodiment, the amount of modified fly ash is 15-20% based on the total weight of cement and aggregate.

[0015] The modified fly ash in the above amount can not only reduce the cracking shrinkage rate of concrete, but also improve the impermeability and freeze-thaw resistance, and ensure the compressive strength of concrete.

[0016] In a preferred embodiment, the particle size of the coarse aggregate is (2.0-2.5) mm, the particle size of the fine aggregate is (0.5-0.8) mm; and the weight ratio of the coarse aggregate to the fine aggregate is 1:(0.5-0.6).

[0017] The coarse aggregate and fine aggregate arranged as above can effectively reduce the porosity in the concrete and improve the density of the concrete.

[0018] In a preferred embodiment, the water-cement ratio of concrete is (0.20-0.25).

[0019] In a preferred embodiment, the mineral fiber comprises basalt fiber; and the organic fiber comprises polyethylene fiber or polypropylene fiber.

[0020] The method for preparing the above concrete comprises the following steps: S1. Preparation of modified fly ash: S11, sieving fly ash, calcium oxide and sodium carbonate respectively with 50-80 mesh, and grinding the sieved powders with a dry ball mill for 30-60 minutes; S12, calcining the powder after ball milling in step S11 at 350-400° C. for 45-60 min; S2. Add cement, modified fly ash, aggregate and water reducing agent in proportion to a forced mixer and dry mix at a speed of 35-45 r / min for 3-4 minutes. Add water and fluidize and stir for 3-4 minutes. Add mineral fiber and organic fiber and continue stirring for 4-5 minutes to obtain concrete. S3, pouring concrete into a mold and curing it to obtain the high-toughness concrete sidewalk brick.

[0021] In a preferred embodiment, in step S1, the weight ratio of fly ash, calcium oxide and sodium carbonate is 100:(10-15):(2-5).

[0022] The present invention first adopts 50-80 mesh sieving to make the particle size uniform, so as to better perform the subsequent ball milling operation, improve the ball milling effect, and realize that the surfaces of all powders are modified through ball milling as much as possible.

[0023] According to the present invention, after ball milling, high-temperature calcination is performed at 350-400° C., so that calcium oxide can excite the fly ash and release active components (Al 2 O 3 , SiO 2 ) in the fly ash.

[0024] In a preferred embodiment, in step S1, the sieved powder is first subjected to microwave treatment for 10-20 minutes and then subjected to ball milling treatment; before step S2, the mineral fiber and the organic fiber are first modified by nano-silicon dioxide.

[0025] The present invention first subjects the powder to microwave treatment, and the microwave can penetrate the powder to generate tiny cracks inside the powder, which is beneficial to the subsequent ball milling treatment and subsequent high-temperature calcination process, and better stimulates the fly ash to release active components (Al2O3, SiO2).

[0026] The present invention can improve the surface roughness of mineral fiber and organic fiber by first modifying mineral fiber and organic fiber respectively with nano silicon dioxide, improve the bonding force between mineral fiber and organic fiber and other substances in concrete, and further improve the anti-cracking effect of concrete.

[0027] The application of the above-mentioned high-toughness concrete sidewalk bricks in municipal roads.

[0028] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention adds modified fly ash, mineral fiber and organic fiber modified by calcium oxide and sodium carbonate into concrete, uses coarse aggregate and fine aggregate in combination, uses a water reducer in combination and reasonably controls the water-binder ratio, so that the prepared high-toughness concrete sidewalk bricks can reduce the shrinkage rate of concrete on the basis of meeting the compressive strength, and improve its impermeability and freeze-thaw resistance. The high-toughness concrete sidewalk bricks can be suitable for municipal road construction and meet construction requirements. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. The schematic implementation mode of the present invention and its description are only used to explain the present invention and are not intended to limit the present invention. The embodiments described below are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0030] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to those of ordinary skill in the art that these specific details do not have to be employed to practice the present invention. In other embodiments, in order to avoid confusing the present invention, known structures, materials or methods are not specifically described. The materials, instruments and reagents used in the following examples, unless otherwise specified, can be obtained from commercial sources. The technical means used in the examples, unless otherwise specified, are conventional means well known to those skilled in the art.

[0031] In order to realize high-toughness concrete sidewalk bricks with excellent crack resistance, impermeability and freeze-thaw cycle resistance on the basis of meeting the compressive strength, this embodiment provides a high-toughness concrete sidewalk brick, including the following components by weight: 500-600 parts of cement, 200-300 parts of modified fly ash, 200-300 parts of mineral fiber, 30-40 parts of organic fiber, 1000-1200 parts of aggregate, 3-5 parts of water reducer, and 100-150 parts of water.

[0032] The modification process of the modified fly ash is as follows: fly ash, calcium oxide and sodium carbonate are mixed by ball milling and then calcined at high temperature; the weight ratio of fly ash, calcium oxide and sodium carbonate is 100: (10-15): (2-5); the temperature of high temperature calcination is 350-400°C.

[0033] The aggregate includes coarse aggregate and fine aggregate. Specifically, the coarse aggregate includes coarse aggregate and fine aggregate; the particle size of the coarse aggregate is (2.0-2.5) mm, the particle size of the fine aggregate is (0.5-0.8) mm; the weight ratio of the coarse aggregate to the fine aggregate is 1: (0.5-0.6).

[0034] Among them, mineral fibers include basalt fibers, which have a diameter of 15μm, a length of 6mm, and a compressive strength of 1050MPa. Basalt fibers are a high-performance fiber material composed of oxides such as silicon dioxide, aluminum oxide, calcium oxide, magnesium oxide, iron oxide, and titanium dioxide. Basalt continuous fibers are not only high in strength, but also have many excellent properties such as electrical insulation, corrosion resistance, and high temperature resistance.

[0035] The organic fiber includes polyethylene fiber or polypropylene fiber, and polyethylene fiber can be used specifically; the polyethylene fiber has a diameter of 20 μm, a length of 18 mm, an elastic modulus of greater than or equal to 3.5 GPa, and a breaking strength of 560 MPa. Polyethylene fiber has the advantages of high tensile strength, high elastic modulus, and low density, and has excellent impact resistance, chemical corrosion resistance, wear resistance, bending resistance, light resistance, cutting resistance, and good insulation performance.

[0036] Among them, cement is ordinary Portland cement.

[0037] The water reducer is preferably a polycarboxylate water reducer or a naphthalene water reducer. The polycarboxylate water reducer and the naphthalene water reducer can significantly reduce the water-cement ratio of the concrete while maintaining the slump of the concrete substantially unchanged, thereby improving the strength and durability of the concrete. The polycarboxylate water reducer and the naphthalene water reducer are both purchased.

[0038] In a preferred case, the amount of modified fly ash is 15-20% based on the total weight of cement and aggregate. By properly controlling the amount of modified fly ash, the density of concrete can be increased as much as possible, and the problem of reduced concrete strength caused by excessive use of modified fly ash can be avoided.

[0039] In a preferred case, the water-cement ratio of concrete is (0.20-0.25). The water-cement ratio is the ratio of water to cement.

[0040] The method for preparing concrete of this embodiment comprises the following steps: S1. Preparation of modified fly ash: S11, sieving fly ash, calcium oxide and sodium carbonate respectively with 50-80 mesh, and grinding the sieved powders with a dry ball mill for 30-60 minutes; S12, calcining the powder after ball milling in step S11 at 350-400° C. for 45-60 min; S2. Add cement, modified fly ash, aggregate and water reducing agent in proportion to a forced mixer and dry mix at a speed of 35-45 r / min for 3-4 minutes. Add water and fluidize and stir for 3-4 minutes. Add mineral fiber and organic fiber and continue stirring for 4-5 minutes to obtain concrete. S3, pouring concrete into a mold and curing it to obtain the high-toughness concrete sidewalk brick.

[0041] In a preferred case, in step S1, the weight ratio of fly ash, calcium oxide and sodium carbonate is 100:(10-15):(2-5).

[0042] In a preferred case, in step S1, the sieved powder is first subjected to microwave treatment for 10-20 minutes and then ball milled.

[0043] In a preferred case, before performing step S2, the mineral fiber and the organic fiber are modified respectively using nano-silicon dioxide. The specific process is: an aqueous solution containing nano-silicon dioxide is prepared by ultrasonic dispersion, and then the mineral fiber and the organic fiber are immersed in the aqueous solution containing nano-silicon dioxide respectively, specifically, nano-silicon dioxide powder and water are mixed in a weight ratio of 1:4, and ultrasonic treatment is performed for 45 minutes, and the surface tension of the fiber is used to make the nano-silicon dioxide particles adhere to the surface of the mineral fiber and the organic fiber, which can enhance the surface roughness of the mineral fiber and the organic fiber.

[0044] This embodiment adds modified fly ash, mineral fiber and organic fiber modified by calcium oxide and sodium carbonate into concrete, uses coarse aggregate and fine aggregate in combination, and uses a water reducer and reasonably controls the water-cement ratio. On the basis of meeting the compressive strength, it is possible to reduce the cracking shrinkage rate of the prepared high-toughness concrete sidewalk bricks, and improve the impermeability and freeze-thaw resistance, so that it can be suitable for the construction of municipal roads.

[0045] The high-toughness concrete sidewalk bricks prepared as above can be used in municipal road construction and laid as sidewalk floor tiles.

[0046] In order to better illustrate the technical effect of this embodiment, the following specific examples are used for illustration: Embodiment 1: A high-toughness concrete sidewalk brick, composed of the following components in parts by weight: 600 parts of cement, 300 parts of modified fly ash, 300 parts of mineral fiber, 40 parts of organic fiber, 1200 parts of aggregate, 5 parts of water reducer, and 140 parts of water.

[0047] The modification process of the modified fly ash is as follows: fly ash, calcium oxide and sodium carbonate are mixed by ball milling, and then calcined at high temperature; the weight ratio of fly ash, calcium oxide and sodium carbonate is 100:15:5; and the temperature of high temperature calcination is 350°C.

[0048] The aggregate includes coarse aggregate and fine aggregate. Specifically, the coarse aggregate includes coarse aggregate and fine aggregate; the particle size of the coarse aggregate is 2.5 mm, the particle size of the fine aggregate is 0.8 mm; and the weight ratio of the coarse aggregate to the fine aggregate is 1:0.6.

[0049] Among them, the cement is ordinary Portland cement; the water reducer is a naphthalene-based water reducer; the mineral fiber is basalt fiber; and the organic fiber is polyethylene fiber.

[0050] The water-to-binder ratio of this embodiment is 0.23.

[0051] In this embodiment, the amount of modified fly ash is 16.7% based on the total weight of cement and aggregate.

[0052] The method for preparing the high-toughness concrete sidewalk bricks of this embodiment comprises the following steps: S1. Preparation of modified fly ash: S11, sieving fly ash, calcium oxide and sodium carbonate respectively through 80 mesh, and grinding the sieved powders by dry ball mill for 60 minutes; S12, calcining the powder after ball milling in step S11 at 350° C. for 50 min; S2. Add cement, modified fly ash, aggregate and water reducing agent in proportion to a forced mixer and dry mix at a speed of 45 r / min for 3 minutes. Add water and fluidize and mix for 4 minutes. Add mineral fiber and organic fiber and continue mixing for 5 minutes to obtain concrete. S3, pouring concrete into a mold and curing it to obtain the high-toughness concrete sidewalk brick.

[0053] Embodiment 2: This embodiment is based on embodiment 1, and the difference from embodiment 1 is that the dosage of each component is different, specifically: A high-toughness concrete sidewalk brick, composed of the following components in parts by weight: 500 parts of cement, 240 parts of modified fly ash, 200 parts of mineral fiber, 30 parts of organic fiber, 1000 parts of aggregate, 3 parts of water reducer, and 115 parts of water.

[0054] The water-to-binder ratio of this embodiment is 0.23.

[0055] In this embodiment, the amount of modified fly ash is 16.0% based on the total weight of cement and aggregate.

[0056] Embodiment 3: This embodiment is based on embodiment 1, and the difference from embodiment 1 is that the dosage of each component is different, specifically: A high-toughness concrete sidewalk brick, composed of the following components in parts by weight: 550 parts of cement, 220 parts of modified fly ash, 240 parts of mineral fiber, 35 parts of organic fiber, 1100 parts of aggregate, 4 parts of water reducer, and 125 parts of water.

[0057] The water-to-binder ratio of this embodiment is 0.23.

[0058] In this embodiment, the amount of modified fly ash is 13.3% based on the total weight of cement and aggregate.

[0059] Embodiment 4: This embodiment is based on embodiment 1, and the difference from embodiment 1 is that the weight ratio of fly ash, calcium oxide and sodium carbonate is different: In this embodiment, the weight ratio of fly ash, calcium oxide and sodium carbonate is 100:10:4.

[0060] Embodiment 5: This embodiment is based on Embodiment 1, and the difference from Embodiment 1 is that: In step S1, the sieved powder is first subjected to microwave treatment for 20 min and then ball milled; Embodiment 6: This embodiment is based on Embodiment 1, and the difference from Embodiment 1 is that: Before performing step S2, the mineral fibers and the organic fibers are modified respectively using nano-silicon dioxide.

[0061] Comparative Example 1: This comparative example is based on Example 1, and the difference from Example 1 is that: Unmodified fly ash is used to replace modified fly ash.

[0062] Comparative Example 2: This comparative example is based on Example 1, and the difference from Example 1 is that: Unmodified fly ash is used to replace modified fly ash, and the amount of fly ash is increased to 400 parts: A high-toughness concrete sidewalk brick, composed of the following components in parts by weight: 600 parts of cement, 400 parts of fly ash, 300 parts of mineral fiber, 40 parts of organic fiber, 1200 parts of aggregate, 5 parts of water reducer, and 140 parts of water.

[0063] Comparative Example 3: This comparative example is based on Example 1, and the difference from Example 1 is that: Use unmodified fly ash to replace modified fly ash, and increase the amount of fly ash to 500 parts: A high-toughness concrete sidewalk brick, composed of the following components in parts by weight: 600 parts of cement, 500 parts of fly ash, 300 parts of mineral fiber, 40 parts of organic fiber, 1200 parts of aggregate, 5 parts of water reducer, and 140 parts of water.

[0064] Comparative Example 4: This comparative example is based on Example 1, and the difference from Example 1 is that: Contains no organic fiber.

[0065] Comparative Example 5: This comparative example is based on Example 1, and the difference from Example 1 is that: Steel fibers are used to replace mineral fibers.

[0066] Comparative Example 6: This comparative example is based on Example 1, and the difference from Example 1 is that: Only calcium oxide is used to modify the fly ash.

[0067] Comparative Example 7: This comparative example is based on Example 1, and the difference from Example 1 is that: The weight ratios of fly ash, calcium oxide and sodium carbonate are different: In this comparative example, the weight ratio of fly ash, calcium oxide and sodium carbonate is 100:8:2.

[0068] Comparative Example 8: This comparative example is based on Example 1, and the difference from Example 1 is that: Sodium hydroxide is used to replace calcium oxide to modify fly ash.

[0069] Comparative Example 9: This comparative example is based on Example 1, and the difference from Example 1 is that: In the process of modifying fly ash, no ball milling treatment is performed.

[0070] After the concrete prepared in Examples 1 to 5 and Comparative Examples 1 to 8 was hardened for 28 days, the compressive strength of each concrete specimen was tested with reference to GB / T50081-2019, the water permeability coefficient of each concrete specimen was tested with reference to GB / T25993-2010; the tensile strength of each concrete specimen was tested with reference to standard T / CECS 10107; the drying shrinkage of each concrete specimen was tested with reference to standard T0574-2020, and the freeze-thaw resistance of each concrete specimen was tested with reference to GB / T 50082-2009 (the mass loss rate of each concrete specimen after 200 test cycles). The results are shown in Table 1: Table 1 From the data in Table 1, we can see that: 1) The present invention adds modified fly ash, mineral fiber and organic fiber to concrete, so that the prepared high-toughness concrete sidewalk bricks have high compressive strength, low cracking risk, high anti-penetration performance and anti-freeze-thaw performance, wherein the compressive strength is greater than 130MPa, the tensile strength is greater than 14.0MPa, the water permeability coefficient is less than 1.5 mm / s, and the drying shrinkage rate is less than 0.15‰; the mass loss rate after 200 cycles is less than 5%.

[0071] 2) When the amount of modified fly ash in concrete decreases, the water permeability coefficient increases and the mass loss rate after 200 cycles increases, that is, the anti-permeability and anti-freeze-thaw properties of the prepared high-toughness concrete sidewalk bricks decrease.

[0072] 3) When fly ash is modified, the amount of calcium oxide, the addition of sodium carbonate, and the use of other alkalis to replace calcium oxide will all lead to a reduction in the modification effect of fly ash, which in turn will lead to a decrease in the anti-penetration and anti-freeze-thaw properties of high-toughness concrete sidewalk tiles when the same amount is added.

[0073] 4) Compared with unmodified fly ash, modified fly ash can effectively improve the anti-permeability and freeze-thaw resistance of high-toughness concrete sidewalk bricks under the same dosage. Increasing the amount of unmodified fly ash can improve the anti-permeability and freeze-thaw resistance of high-toughness concrete sidewalk bricks to a certain extent, but it still cannot be compared with modified fly ash with a lower addition amount. On the contrary, the compressive strength of high-toughness concrete sidewalk bricks decreases due to the increase in the addition amount of unmodified fly ash.

[0074] 5) Ball milling treatment can improve the modification effect of fly ash to a certain extent.

[0075] 6) The combination of mineral fiber and organic fiber is used to improve the anti-penetration and anti-freeze-thaw properties of high-toughness concrete sidewalk tiles and reduce the risk of concrete cracking.

[0076] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high-toughness concrete sidewalk brick, characterized in that: It includes the following components by weight: 500-600 parts of cement, 200-300 parts of modified fly ash, 200-300 parts of mineral fiber, 30-40 parts of organic fiber, 1000-1200 parts of aggregate, 3-5 parts of water reducer, 100-150 parts of water; The modified fly ash is modified by mixing fly ash, calcium oxide and sodium carbonate by ball milling and then calcining at high temperature; Wherein, the aggregate includes coarse aggregate and fine aggregate.

2. The high-toughness concrete sidewalk brick according to claim 1, characterized in that: The weight ratio of the fly ash, the calcium oxide and the sodium carbonate is 100:(10-15):(2-5).

3. The high-toughness concrete sidewalk brick according to claim 1, characterized in that: The temperature of the high temperature calcination is 350-400°C.

4. The high-toughness concrete sidewalk brick according to claim 1, characterized in that: The amount of the modified fly ash is 15-20% based on the total weight of the cement and the aggregate.

5. The high-toughness concrete sidewalk brick according to claim 1, characterized in that: The particle size of the coarse aggregate is (2.0-2.5) mm, and the particle size of the fine aggregate is (0.5-0.8) mm; the weight ratio of the coarse aggregate to the fine aggregate is 1:(0.5-0.6).

6. The high-toughness concrete sidewalk brick according to claim 1, characterized in that: The water-cement ratio of the concrete is (0.20-0.25).

7. A high toughness concrete sidewalk brick according to any one of claims 1 to 6, characterized in that: The mineral fiber includes basalt fiber; the organic fiber includes polyethylene fiber or polypropylene fiber.

8. The method for preparing the high-toughness concrete sidewalk brick according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Preparation of modified fly ash: S11, sieving fly ash, calcium oxide and sodium carbonate respectively with 50-80 mesh, and grinding the sieved powders with a dry ball mill for 30-60 minutes; S12, calcining the powder after ball milling in step S11 at 350-400° C. for 45-60 min; S2, adding the cement, the modified fly ash, the aggregate and the water reducing agent in proportion into a forced mixer and dry mixing the mixture at a speed of 35-45 r / min for 3-4 minutes, adding the water and fluidizing stirring for 3-4 minutes; adding the mineral fiber and the organic fiber, and continuing stirring for 4-5 minutes to obtain concrete; S3, pouring concrete into a mold and curing it to obtain the high-toughness concrete sidewalk brick.

9. The preparation method according to claim 8, characterized in that: In step S1, the sieved powder is first subjected to microwave treatment for 10-20 minutes and then subjected to ball milling treatment; before step S2, the mineral fiber and the organic fiber are first modified by using nano-silicon dioxide.

10. Use of the high-toughness concrete sidewalk brick according to any one of claims 1 to 7 in municipal roads.